Tear film and lid margin changes in patients with different types of primary pterygium - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Ithnin, Mohd. Hafidz (Universitas Islam Agung Sultan Semarang, 2019)
Purpose. This study aimed to evaluate tear film and lid margin changes in patients with different types of primary pterygium. Methods. A total of 123 participants comprises of normal patients (n=30), patients with type I pterygium (n=30), type II pterygium (n=32) and type III pterygium (n=31) without ocular pathologies were selected from patients who visited an ophthalmology clinic. Ocular surface disease index scores (OSDI), meibomian gland expression (MGE), lid margin abnormality (LM) scores, tear break-up time (TBUT), Schirmer test (SIT) value and multiple tear meniscus values; the lower tear meniscus height (TMH), tear meniscus depth (TMD) and tear meniscus area (TMA) measured using time-domain ocular coherence tomography were performed. Comparative analyses between groups were performed for all parameters. A statistical significance level of P < 0.05 was considered. Association of OSDI with LM abnormality scores, MGE and tear break-up time (TBUT) with all pterygium types were examined. Results. All parameters were significantly higher in pterygium patients compared to controls (P < 0.001). However, TBUT scores, SIT scores, the lower TMH, TMD and TMA values revealed no significant difference between pterygium type I and control group (P > 0.05). Correlation analysis revealed LM abnormality, MGE and TBUT were significantly correlated with OSDI scores pterygium patients. Conclusions. Advance pterygium cause alteration of tear film and lid margin, which is associated with ocular discomfort. Early detection of lid margin changes seems to be important to understand the relationship between pterygium, tear film functions and changes of the ocular surface.